Anatomical theatre place of Knowledge – the pivotal role of anatomist in its realization - Armocida, Emanuele; Ruggeri, Alessandro (Italian Journal of Anatomy and Embryology, 2017)
Human anatomy dissection represented a cornerstone in the evolution of medicine and modern scientific thought. The anatomical theatres, some of which are considered true masterpieces of architecture, are the place where concretely men learned to know themselves with a scientific method. Anatomists had a pivotal role in the buildings of anatomical theatres, using their knowledge in the research process of more functional architectures for demonstrative and experimental science. Antonio Scarpa (1752-1832) is an emblematic figure in this scenario. He studied anatomy at the University of Padua in the oldest permanent anatomical theatre of the world, originate in 1594 from a joint project conceived by Paolo Sarpi, scientist and church reformer, and Hieronymus Fabricius Ab Aquapendente, anatomist. In 1772, Scarpa became professor at the University of Modena. Bearing witness to the architectural value of the theatre in Padua is the fact that in 1774 Scarpa, involved in the planning for an anatomical theatre in Modena, had the professor of surgery in Padua, Girolamo Vandelli, send him a wooden model of the theatre there. Another project, less expensive, was selected instead. Later, in 1783, Scarpa was made professor of anatomy at the University of Pavia and promptly he promoted the building of an anatomical theatre there. The building was concluded in 1785, its semicircular layout is modeled on ancient theatres and the Palladian Olympic Theatre of Vicenza. Today, most of the anatomical theatres are lost or forgotten. The Thesa project will provide a census of anatomical theatres, both survived and not, which will allow us to identify connections among them, among the anatomists who studied there and the mutual influences that characterize their form. We believe the achievement of these objectives defines the essential conditions necessary to regain full awareness of the value of anatomical theatres in both the academic and popular contexts, thus creating a fertile cultural basis for new initiatives that can continue the quest for knowledge undertaken in the past in these places. From an architectural and evocative perspective, they are and will remain places where man puts himself at the centre and at the same time observes himself.